Costs and Mortality Associated With Multidrug-Resistant Healthcare-Associated Acinetobacter Infections. (13th July 2016) - Nelson, Richard E.; Schweizer, Marin L.; Perencevich, Eli N.; Nelson, Scott D.; Khader, Karim; Chiang, Hsiu-Yin; Chorazy, Margaret L.; Blevins, Amy; Ward, Melissa A.; Samore, Matthew H.
Abstract : BACKGROUND: Our objective was to estimate the per-infection and cumulative mortality and cost burden of multidrug-resistant (MDR) Acinetobacter healthcare-associated infections (HAIs) in the United States using data from published studies. METHODS: We identified studies that estimated the excess cost, length of stay (LOS), or mortality attributable to MDR Acinetobacter HAIs. We generated estimates of the cost per HAI using 3 methods: (1) overall cost estimates, (2) multiplying LOS estimates by a cost per inpatient-day ($4, 350) from the payer perspective, and (3) multiplying LOS estimates by a cost per inpatient-day from the hospital ($2, 030) perspective. We deflated our estimates for time-dependent bias using an adjustment factor derived from studies that estimated attributable LOS using both time-fixed methods and either multistate models (70.4% decrease) or matching patients with and without HAIs using the timing of infection (47.4% decrease). Finally, we used the incidence rate of MDR Acinetobacter HAIs to generate cumulative incidence, cost, and mortality associated with these infections. RESULTS: Our estimates of the cost per infection were $129, 917 (method 1), $72, 025 (method 2), and $33, 510 (method 3). The pooled relative risk of mortality was 4.51 (95% CI, 1.10–32.65), which yielded a mortality rate of 10.6% (95% CI, 2.5%–29.4%). With an incidence rate of 0.141 (95% CI, 0.136–0.161) per 1, 000 patient-days at risk, we estimated an annual cumulative incidence of 12, 524 (95% CI, 11, 509–13, 625) in the United States. CONCLUSION: The estimates presented here are relevant to understanding the expenditures and lives that could be saved by preventing MDR Acinetobacter HAIs. Infect Control Hosp Epidemiol 2016;1–7